2014
DOI: 10.1017/s1368980014000962
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between food literacy and dietary intake in adolescents: a systematic review

Abstract: Food literacy may play a role in shaping adolescents' dietary intake. More rigorous research methods are required to effectively assess the causality between food literacy and adolescents' dietary intake in order to confirm the extent of the relationship. Evidence recommends public health practitioners and policy makers consider new public health strategies that focus on increasing understanding of food literacy in adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
241
1
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(266 citation statements)
references
References 42 publications
11
241
1
13
Order By: Relevance
“…A total of thirty studies were included in the review. Of these, 5 studies simultaneously addressed both food/nutrition literacy definitions and its components [18,22,25,38,39], only 17 studies defined food/nutrition literacy [19,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55] and 8 focused on food/nutrition literacy dimensions [17,24,56,57,58,59,60,61]. Based on the literature, components of nutrition literacy are based on Nutbeam’s concept of health literacy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of thirty studies were included in the review. Of these, 5 studies simultaneously addressed both food/nutrition literacy definitions and its components [18,22,25,38,39], only 17 studies defined food/nutrition literacy [19,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55] and 8 focused on food/nutrition literacy dimensions [17,24,56,57,58,59,60,61]. Based on the literature, components of nutrition literacy are based on Nutbeam’s concept of health literacy.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding determinants of unhealthy behaviors is therefore crucial. One way for understanding the reasons behind the nutrition-related problems and behaviors among children and adolescents is assessment of their food and nutrition literacy level [17]. …”
Section: Introductionmentioning
confidence: 99%
“…This learning area orients on individual and family well‐being in their day‐to‐day living through building student capacity including the application of food and nutrition knowledge into practice such as developing food skills . It is important to know how food literacy is taught and which aspects of food literacy are emphasized at secondary schools as a recent systematic review indicated that food literacy may influence adolescents' dietary intake . There is limited understanding about which aspects of food literacy are being emphasized by home economics teachers (HETs), and which aspects are perceived as the most important for improving adolescents' dietary intake.…”
mentioning
confidence: 99%
“…On the other hand, having a muscular appearance is critical to male body image and may influence increased protein intake among boys . While some evidence suggests knowledge is a factor in determining adolescent eating behaviours others contend it does not have a significant influence . Furthermore evidence suggests that even if young people are aware of the health impact of unhealthy food this is unlikely to influence their food intake because they believe nutrition‐related diseases are not likely to develop until they are much older .…”
Section: Introductionmentioning
confidence: 99%